Self-Rated Healthy Life Expectancy Changes in Jiangxi Province of China by Gender and Urban–Rural Differences, 2013–2018 - Liu, Zhitao; Zheng, Huilie; Wu, Yuhang; Wang, Shengwei; Liu, Yong; Hu, Songbo (Frontiers in Public Health, 2021)
Background: Globalization has brought about rapid economic and technological development, and the life expectancy of human beings is constantly increasing. However, it is not clear whether an increase in life expectancy will result in an increase in healthy life expectancy (HLE). This study evaluates trends of self-rated healthy life expectancy (SRHLE) of residents aged 15 and older in Jiangxi Province of China from 2013 to 2018 and analyzes the gender differences and urban-rural differences. And provide a basis for the formulation of relevant public health policies. Methods: Based on two National Health Services Survey databases of Jiangxi in 2013 and 2018 as well as infant mortality rate and under 5 mortality rates from the Health Commission of Jiangxi, the Sullivan method was used to calculate SRHLE. Results: SRHLE decreased from 56.55 to 55.54 years and from 60.00 to 57.87 years for men and women at age 15-19 from 2013 to 2018, respectively. The SRHLE of women aged 15-19 were 3.45 and 2.34 years higher than men in 2013 and 2018, respectively. The SRHLE of urban men aged 15-19 were 2.9 and 4.46 years higher than rural men in 2013 and 2018, respectively; and for urban women aged 15-19 were 3.28 and 5.57 years higher than rural women. Conclusions: The decreased SRHLE indicated that the self-rated health (SRH) status of residents in Jiangxi has become worse and it provided evidence for the expansion of morbidity, this was mainly due to the increased in the prevalence of chronic diseases and the enhancement of residents' health awareness. Policy efforts are necessary to control the increased morbidity of chronic diseases and reduce gender and urban-rural differences in the quantity and quality of years to be lived.